Provable security : 12th International Conference, ProvSec 2018, Jeju, South Korea, October 25-28, 2018, Proceedings /: 12th International Conference, ProvSec 2018, Jeju, South Korea, October 25-28, 2018, Proceedings. (2018) - Unknown
No abstract available